THE EFFICACY OF GIMKIT TO INCREASE STUDENT’S READING ACHIEVEMENT OF HORTATORY EXPOSITION TEXT AT SMAN 1 SUTOJAYAN - Septi Wulandari, sabrina; Supriyono; Aini, Miza Rahmatika; Fadhilawati, Dian (Universitas Islam Balitar, 2024)
At First Sutojayan State Senior High School, the purpose of this study is to ascertain whether Gimkit is effective in raising students' reading achievement of a hortatory exposition text. This study employed a pre-experimental, quantitative methodology with a single group pre- and post-testing. Thirty-five students from SMAN 1 Sutojayan's XI MIPA 4 served as the research sample. A pretest, three treatments, and a posttest were given to the students in order of administration. Pre- and post-test data were collected, and the Paired Samples T-Test in SPSS version 25 was used to analyze the data. The average score for the pre-test was 74.4, while the average score for the post-test was 81.5, according to the researchers' analysis of the pre- and post-test results. With a significance value of 0.000, the study's findings showed a significant difference between the experimental group's pre- and post-test scores. The t count of 6.583 supports these findings, and since the t table is 1.69092 (t count 6.583 > t table 1.69092), these findings demonstrate that Ha is accepted and H0 is rejected. This implies that kids' reading achievement is improved when they utilize the Gimkit program. Consequently, it is advised that teachers utilize the Gimkit program when teaching reading in the classroom.